A Compact Fourth-Order Finite Difference Scheme for the Improved Boussinesq Equation with Damping Terms (Journal of Computational Mathematics, 2018)
In this paper, a compact finite difference method is presented for solving the initial boundary value problems for the improved Boussinesq equation with damping terms. The fourth-order equation can be transformed into a first-order ordinary differential system, and then, the classical Padé approximation is used to discretize spatial derivative in the nonlinear partial differential equations. The resulting coefficient matrix for the semi-discrete scheme is tri-diagonal and can be solved efficiently. In order to maintain the same order of convergence, the classical fourth-order Runge-Kutta method is the preferred method for explicit time integration. Soliton-type solutions are used to evaluate the accuracy of the method, and various numerical experiments are designed to test the different effects of the damping terms.
Keywords: Compact finite difference method; Improved Boussinesq equation; Stokes damping; Hydrodynamic damping; Runge-Kutta method.